Active Surveillance vs Immediate Treatment—Which Has a Greater Financial Incentive for Urologists?. Issue 3 (30th May 2020) - Zhang, Zheng; Modi, Parth K.; Shahinian, Vahakn; Herrel, Lindsey A.; Dupree, James M.; Yan, Phyllis; Denton, Brian T.
Abstract: Introduction: We compared cumulative reimbursement to urologists following implementation of surveillance vs immediate treatment. Active surveillance for prostate cancer is widely considered beneficial and cost-effective for low risk patients, although many still receive immediate therapy. It is unknown whether reduced reimbursement may be a barrier to urologists recommending surveillance. Methods: We used Medicare claims and a validated natural history model for low risk prostate cancer to simulate annual reimbursements associated with active surveillance and immediate treatments, including surgery and radiation therapy. The model accounts for misclassification due to biopsy under sampling, grade progression and discontinuation of surveillance due to patient preferences. Results: Active surveillance provided approximately $907 to $2, 041 less in the net present value of expected cumulative reimbursements for urologists over 10 years ($1, 711.80 to $2, 740.40 less over 5 years) compared to initial treatment. Sensitivity analysis showed that use of magnetic resonance imaging/ultrasound fusion based biopsy and frequency of biopsies and clinic visits under surveillance are major sources of uncertainty regarding reimbursement. Conclusions: Urologists have little financial incentive to implement active surveillance. New payment models may be needed to bring financial incentives in line with the recommended treatment for patients with low risk prostate cancer.